CUSTOMS CONTROL OF FOREIGN ECONOMIC ACTIVITY IN THE AGRICULTURAL SECTOR: ECONOMIC AND LEGAL ASPECTS - Kyrylo Voronov; Eduard Ivanchenko; Viktoriia Kachuriner (Baltic Journal of Economic Studies)
Relevance. The agricultural sector plays a pivotal role in Ukraine's economy, with a considerable degree of reliance on the effective execution of foreign economic activity (FEA). It remains a vital component of Ukraine's economy, ensuring the country's food security and contributing to stable exports, which represent a primary source of foreign currency earnings. The ongoing conflict has introduced a number of new challenges to customs control, including the disruption of logistics routes, an increased risk of smuggling, and the necessity for the implementation of accelerated customs procedures for critical goods. Concurrently, it becomes increasingly crucial to adhere to legislative norms and international standards in order to prevent violations and guarantee effective border control. In wartime conditions, the optimisation of customs procedures, such as the simplification and acceleration of the clearance of agricultural products, in conjunction with the strengthening of control over imports and exports to avoid unfair practices, becomes particularly relevant. Objective. The objective of the study is to conduct a comprehensive analysis of the economic and legal aspects of customs control in the FEA of Ukraine's agricultural sector. Methodology. The research methodology encompasses a range of techniques, including comparative analysis, policy analysis, and case analysis. Results. The study examines the economic and legal aspects of customs control in the FEA of the agricultural sector. It analyses the main legislative acts regulating the customs control of agricultural products in Ukraine, as well as international standards and rules affecting customs clearance procedures. Special attention is given to the challenges faced by agricultural enterprises in export-import operations during wartime, and proposals are made for improving customs regulation to increase the efficiency of the sector in the global economy.